Insights From Industry, Educators, and Graduates (Enhancing Financial Sustainability and Competency Development in Maritime Education) - Rosna Yuherlina Siahaan; Harita Julie Zefanya Matondang (Dharma Ekonomi, 2024)
The maritime industry requires financially literate and strategically competent professionals to navigate challenges in shipping management, business sustainability, and economic resilience. However, vocational maritime education often lacks practical financial training and sustainability-driven business strategies, creating gaps between academic learning and industry needs. This research addresses these gaps by analyzing how maritime education aligns with financial sustainability and business competency development. Unlike previous studies that separately examine maritime education or financial sustainability, this research integrates expert insights, graduate experiences, and educator perspectives to develop a holistic framework for maritime business and financial training. The findings contribute to policy discussions on improving vocational curricula and bridging industry-academia gaps. This study investigates the effectiveness of maritime vocational education in developing competencies in financial decision-making, economic resilience, and business sustainability. It evaluates curriculum alignment with industry demands and identifies key areas for enhancement. A qualitative research design was used, incorporating semi-structured interviews with 13 maritime professionals, 4 educators, and 33 graduates. Thematic analysis was applied to assess vocational training effectiveness in financial sustainability and business resilience. Findings reveal strong technical competency but gaps in financial literacy and sustainability-driven business strategies. Maritime education programs scored 9/10 in effectiveness, but practical applications of financial decision-making and risk management need reinforcement. This study provides actionable insights for vocational training reforms, emphasizing applied financial education, industry collaboration, and sustainability-driven business strategies. The findings support future curriculum development to equip maritime professionals with enhanced financial and managerial competencies for industry leadership.